PENGARUH CEKAMAN KEKERINGANPADA PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS KEDELAI (Glycine max L Merr) LOKAL - ONGKO CAHYONO (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2019)
The study aimed to assess the response of four varieties of soybean (Argomulyo, Grobogan, Local Wonogiri dan Local Karanganyar) grown in different soil water content (100%, 70% and 40% of the field capacity). This pot experiment was done in the green house in Sumber Banjarsari Surakarta (at about 98 metres above sea level), using Factorial Experimental Design. The research consluded that soil water content as low as 70% and 40% of field capacity restrain plant growth and seed yield of all soybean varieties. This was indicated by the reduction of plant height, dry weight ofÂ leaf, dry weight of root, dry weight of root and shoot and seed yield.Â Water stress decreased significantly rhe vegetative growth of Argomulyo dan Grobogan varieties, but decreased significantly seed yield of bth local Wonogiri and Karangayar varieties. The varieties of Argomulyo and Grobogan are more drought tolerant compared to the local varieties ofÂ Wonogiri and Karanganyar.